2019
DOI: 10.3390/ijerph17010053
|View full text |Cite
|
Sign up to set email alerts
|

Absenteeism during Menstruation among Nursing Students in Spain

Abstract: Absenteeism can clearly have a negative impact on academic performance among university students. Certain experiences or symptoms such as menstrual pain are very common in women and can lead to absenteeism. The current study was aimed at examining the presence of menstrual experiences or symptoms and their impact upon absenteeism among healthy (illness-free) female university nursing students in Spain. A total of 299 students participated in this research, which was a descriptive cross-sectional, observational… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
43
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 44 publications
(52 citation statements)
references
References 45 publications
8
43
1
Order By: Relevance
“…Up to 62.8% of participants reported absenteeism due to menstrual pain, similar to the 60.5% reported by nursing students at other Spanish universities [ 2 ] but far higher than the 20.1% found in the meta-analysis published in 2019 [ 1 ]. This difference is striking and may be due to the fact that the meta-analysis included studies with non-homogeneous sample populations, including secondary school students and university students of various disciplines.…”
Section: Discussionsupporting
confidence: 58%
See 4 more Smart Citations
“…Up to 62.8% of participants reported absenteeism due to menstrual pain, similar to the 60.5% reported by nursing students at other Spanish universities [ 2 ] but far higher than the 20.1% found in the meta-analysis published in 2019 [ 1 ]. This difference is striking and may be due to the fact that the meta-analysis included studies with non-homogeneous sample populations, including secondary school students and university students of various disciplines.…”
Section: Discussionsupporting
confidence: 58%
“…Ultimately, 16 women agreed to participate in the project, however three did not complete it in full. Taking into consideration the absenteeism variable (dichotomous: yes/no) as the main variable concerning the repercussions of dysmenorrhea in the life of university women for this study and the calculation of its proportion based on the previous literature [ 2 ], retrospective calculations revealed that the power of the contrast was 0.97.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations